Factors predictive of inaccurate determination of horizontal extent of intestinal‐type early gastric cancers during endoscopic submucosal dissection: A retrospective analysis. Issue 6 (12th March 2013) - Asada‐Hirayama, Itsuko; Kodashima, Shinya; Goto, Osamu; Yamamichi, Nobutake; Ono, Satoshi; Niimi, Keiko; Mochizuki, Satoshi; Konno‐Shimizu, Maki; Mikami‐Matsuda, Rie; Minatsuki, Chihiro; Takahashi, Yu; Matsusaka, Keisuke; et al.
Abstract : Background: Certain tumor characteristics may pose challenges when endoscopically determining the horizontal extent of early gastric cancers (EGC). In the present study, clinicopathological features related to inaccurate endoscopic evaluation of horizontal extent of intestinal‐type EGC were analyzed. Patients and Methods: We analyzed 431 lesions with intestinal‐type EGC treated by endoscopic submucosal dissection (ESD) at our hospital. We focused on whether pretreatment demarcation was accurate by comparing positional relationships between marking dots and tumor edges in resected specimens, and factors related to inaccurate evaluation were analyzed. Gender, age, tumor size, location, circumference, depth, ulceration, macroscopic type, presence of a flat (0‐IIb) component, predominant histological type, mixture of diffuse‐type adenocarcinoma, mixed histology, and use of magnification endoscopy with narrow band imaging were analyzed. Reasons for inaccurate evaluation were also investigated by re‐examining endoscopic images and prepared histological slides. Results: Rate of inaccurate evaluation of horizontal extent was 7.4% (32/431 lesions). Multivariate analysis revealed the following significant independent variables contributing to inaccurate endoscopic evaluation: presence of a flat component, large size, and predominant histological findings of moderately differentiated adenocarcinoma. Re‐examination of prepared histological slides of inaccurately evaluated cases revealed a marginal flat spreading area in 28 of the 32 lesions (87.5%). In 14 of the 32 lesions (43.8%), tumor margins were composed of moderately differentiated adenocarcinoma. Conclusions: For lesions with a flat component, large lesions, and moderately differentiated adenocarcinoma, determination of the horizontal extent can be challenging in EGC indicated for ESD, even with the best available endoscopic tools.